Лімфаденектомія за папілярного та фокулярного раків щитоподібної залози - Вовк, В. С.; Цьолко, Т. Р.; Стернюк, Ю. М. (Clinical Endocrinology and Endocrine Surgery, 2012)
There is still unresolved debate about the optimal surgical management of papillary (PTC) and follicular (FTC) thyroid cancer regarding lymph node dissection. So far the guidelines recommend the same extent of surgery for both tumors. This study is based on 462 patients with DTC – 365 with PTC, 97 with FTC. The extent of surgery, tumor size, and pN status were analysed. The results were compared with those in the current literature. Tumors ≤20 mm in size were found significantly more often in PTC than FTC (69,5% vs. 27,8%, p<0,001). Positive lymph nodes were found significantly more often in PTC than as well (32,9% vs. 5,2%, p<0,001). In PTC up to 10mm and from 11 mm to 20 mm in size, 16,0% and 41,8% (p<0,001) of patients, respectively, showed positive lymph nodes. In FTC positive lymph nodes occurred only in tumor >25 mm. Duo to prevalence and importance of lymph node metastasis differing between PTC and FTC, we recommend treating both tumor entities differently. For PTC a more extended lymph dissection is necessary, even in tumors ≤20 mm. In small FTC it seems adequate to limit the operation to thyroidectomy without prophylactic lymph dissection.